2016
DOI: 10.1177/1352458516643600
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of spasticity in multiple sclerosis: Systematic review and consensus paper

Abstract: Background and objectives: Treatment of spasticity poses a major challenge resulting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
80
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 86 publications
1
80
0
4
Order By: Relevance
“…Sativex ® is a new, add-on treatment option for patients with moderate to severe MSS and it is administered as a spray containing the active substances delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) at a ratio of 1: 1. The findings from clinical studies have shown that THC:CBD oromucosal spray reduces spasticity in MS patients and is well-tolerated [10][11][12] , and it is recommended as a second-or third-line option in the most recent ECTRIMS endorsed MSS management guidance paper [13] . This prospective, multicentre, non-interventional observational study was performed to collect real-life data on the effectiveness and tolerability of THC:CBD oromucosal spray in everyday clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Sativex ® is a new, add-on treatment option for patients with moderate to severe MSS and it is administered as a spray containing the active substances delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) at a ratio of 1: 1. The findings from clinical studies have shown that THC:CBD oromucosal spray reduces spasticity in MS patients and is well-tolerated [10][11][12] , and it is recommended as a second-or third-line option in the most recent ECTRIMS endorsed MSS management guidance paper [13] . This prospective, multicentre, non-interventional observational study was performed to collect real-life data on the effectiveness and tolerability of THC:CBD oromucosal spray in everyday clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…There is a reduction in motor dysfunction and pain, observed in meta-analysis of several clinical studies. However, an increased incidence of non-serious side effects was also reported (Wade et al, 2010; Otero-Romero et al, 2016). Importantly, a review by the National Institute for Health and Care Excellence in the United Kingdom, recommended against the use of Sativex® to treat spasticity in people with MS because it is not a cost effective treatment (Multiple sclerosis in adults: management | 1-recommendations | Guidance and guidelines | NICE, 2014).…”
Section: Multiple Sclerosismentioning
confidence: 89%
“…Importantly, a review by the National Institute for Health and Care Excellence in the United Kingdom, recommended against the use of Sativex® to treat spasticity in people with MS because it is not a cost effective treatment (Multiple sclerosis in adults: management | 1-recommendations | Guidance and guidelines | NICE, 2014). For a recent and comprehensive analysis of clinical studies see the work of Otero-Romero et al (2016). …”
Section: Multiple Sclerosismentioning
confidence: 99%
“…If not satisfactory they should be supported as described by Otero-Romero et al [13], adding cannabis-based drugs, peripherally acting injected muscle relaxants (botulinum toxin, local phenol injections) or intrathecal therapies (baclofen or phenol), together with a complete rehabilitation program providing continuous physical therapy.…”
Section: Introductionmentioning
confidence: 99%